Meningkatkan Minat Belajar IPAS Menggunakan Model Cooperative Learning Tipe (TGT) pada Siswa Kelas IV - Ainun Rofiah; Vivi Rulviana; Rakini Rakini (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of the research is to determine the interest of class IV SDN 02 Taman Madiun in learning science and science material on plant parts by applying the TGT type cooperative learning model. Using the Classroom Action Research (PTK) method which was carried out in two cycle meetings. Stages include observation, planning, implementation, and reflection consisting of each cycle. 7 class IV students at SDN 02 Taman Madiun were used as research subjects. Data collection instruments consist of interviews, questionnaires, observations and documentation. The results of the research prove that fourth grade students' interest in learning science and science material about plant parts has increased after implementing the TGT type cooperative model. The percentage of interest results increased, initially 68.52% in the first practice cycle meeting, then increasing to 85.26% after the second practice cycle meeting. These results become an alternative strategy to achieve interest in learning for class IV SDN 02 Taman as expected through the implementation of the TGT type cooperative model.